THE FORMATION AND DEVELOPMENT OF CONSTRUCTION CLUSTERS IN THE CONDITIONS OF REGIONAL DEVELOPMENT - M. A., Abduraxmanov (Journal of Higher Education and Academic Advancement, 2024)
Objective: This research aims to evaluate the effectiveness of regional investment construction clusters by addressing gaps in existing models, specifically those that overlook key elements such as inter-network relationships, cluster management, and transaction cost savings. Methods: A systemic approach combining quantitative and qualitative analysis was employed to examine the dynamics of regional construction clusters. The study focused on small, medium, and large construction firms, intermediaries, and public-private partnerships, using a lifecycle analysis to assess cluster development stages from emergence to decline. Results: The study revealed that current models fail to consider the complexities of cluster interactions and the role of public-private partnerships in fostering regional development. Key findings highlight the need for a balanced management structure that allows both centralization and autonomy, promoting collaborative outcomes among stakeholders. Novelty: This research introduces a holistic approach to cluster evaluation, incorporating both tangible and intangible factors such as social development, transaction cost savings, and the integration of local and regional resources. The findings offer new insights into managing investment-construction clusters for sustainable growth and socio-economic development.